Peranan Guru Terhadap Peningkatan Motivasi Belajar Siswa Kelas V di Sekolah Dasar Negeri 09 Tanjung Lay - Ulandari, Lestari; Waridah, Waridah; Rudiansyah, Eko (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2025)
Abstract: This research aims to determine the role of teachers in increasing student learning motivation. This research uses qualitative research methods using a descriptive approach.This research was carried out in class V of SD Negeri 09 Tanjung Lay. The instruments used in this research were observation sheets and interviews. Sources of research data were obtained from class teachers, Islamic religious education teachers, and physical education teachers, as well as 26 class V students consisting of 17 male students and 9 female students. The results of this research suggest six teacher roles in increasing student learning motivation, namely making students active in teaching and learning activities, creating a conducive classroom atmosphere, creating varied learning methods, increasing enthusiasm and passion for teaching, giving awards, and creating activities that engage students in class. Teachers play their role in increasing students' learning motivation, such as providing grades, awards and praise. There are quite a lot of obstacles faced by teachers in carrying out their role in increasing student learning motivation, such as student characteristics, limited classroom situations and conditions and the number of students exceeding the quota.Keywords: The Role Of The Teacher, Learning Motivation, Elementary School Student. Abstrak: Penelitian ini bertujuan untuk mengetahui peranan guru terhadap peningkatan motivasi belajar siswa. Penelitian ini menggunakan metode penelitian kualitatif dengan menggunakan pendekatan deskriptif. Penelitian ini dilaksanakan dikelas V SD Negeri 09 Tanjung Lay. Instrumen yang digunakan dalam penelitian ini yaitu observasi dan lembar wawancara. Sumber data penelitian yang di peroleh dari wali kelas, guru pendidikan agama Islam, dan guru pendidikan jasmani dan olahraga, serta siswa kelas V sebanyak 26 siswa yang terdiri dari 17 siswa laki-laki dan 9 siswa perempuan. Hasil penelitian ini mengemukakan enam peranan guru terhadap peningkatan motivasi belajar siswa yaitu menjadikan siswa yang aktif dalam kegiatan belajar mengajar, menciptakan suasana kelas yang kondusif, menciptakan metode pembelajaran yang bervariasi, meningkatkan antusias dan semangat dalam mengajar, memberikan penghargaan, serta menciptakan aktivitas yang melibatkan siswa dalam kelas. Guru melakukan peranannya terhadap peningkatan motivasi belajar siswa seperti memberikan nilai, penghargaan, dan pujian. Kendala yang dihadapi guru dalam menjalankan peranannya terhadap peningkatan motivasi belajar siswa seperti karakteristik siswa, situasi dan kondisi kelas yang terbatas serta jumlah siswa yang melebihi kuota.Kata Kunci: Peranan Guru, Motivasi Belajar, Siswa Sekolah Dasar.